Triggered contraction of self-assembled micron-scale DNA nanotube rings - Illig, Maja; Jahnke, Kevin; Weise, Lukas P.; Scheffold, Marlene; Mersdorf, Ulrike; Drechsler, Hauke; Zhang, Yixin; Diez, Stefan; Kierfeld, Jan; Göpfrich, Kerstin (Nature Communications, 2024)
Contractile rings are formed from cytoskeletal filaments during cell division. Ring formation is induced by specific crosslinkers, while contraction is typically associated with motor protein activity. Here, we engineer DNA nanotubes and peptide-functionalized starPEG constructs as synthetic crosslinkers to mimic this process. The crosslinker induces bundling of ten to hundred DNA nanotubes into closed micron-scale rings in a one-pot self-assembly process yielding several thousand rings per microliter. Molecular dynamics simulations reproduce the detailed architectural properties of the DNA rings observed in electron microscopy. Theory and simulations predict DNA ring contraction - without motor proteins - providing mechanistic insights into the parameter space relevant for efficient nanotube sliding. In agreement between simulation and experiment, we obtain ring contraction to less than half of the initial ring diameter. DNA-based contractile rings hold promise for an artificial division machinery or contractile muscle-like materials.
Gesehen am 16.04.2024